Conflict exposure and expected victimization in Nigeria - Daniel Tuki (Behavioral Sciences of Terrorism and Political Aggression, 2024)
Although the Northern Nigerian state of Kaduna has the second highest incidence of violent conflicts among Nigeria's 36 states, the population generally reports a low level of expected victimization. A large-N survey conducted in the state in 2021 showed that 65% of the population believe they are unlikely to be directly affected by violent conflict in the future. This is surprising, given that 42% of respondents experienced at least 10 conflict incidents within a 100.25emkm radius around their dwellings between 1997 and 2020. Ordered logit regressions reveal that the more individuals are exposed to conflict, the less worried they are about getting victimized. The negative correlation between violent conflict and expected victimization might be due to the existential threat posed by violent conflict, which prompts people to rely more heavily on their ethnoreligious kinship ties for both material and non-material support. This, in turn, attenuates their fear of victimization.
https://doi.org/10.7910/DVN/6WYTJZ
Keywords: 320; Violent conflict; expected victimization; social cohesion; religion; ethnicity; Kaduna State; Nigeria